Rapid detection of Puccinia triticina causing leaf rust of wheat by PCR and loop mediated isothermal amplification. - C Manjunatha (PLoS ONE, 2018)
Leaf rust of wheat caused by Puccinia triticina has significant impact on wheat production worldwide. Effective and quick detection methodologies are required to mitigate yield loss and time constraints associated with monitoring and management of leaf rust of wheat. In the present study, detection of P. triticina has been simplified by developing a rapid, reliable, efficient and visual colorimetric method i.e., loop mediated isothermal amplification of DNA (LAMP). Based on in silico analysis of P. triticina genome, PTS68, a simple sequence repeat was found highly specific to leaf rust fungus. A marker (PtRA68) was developed and its specificity was validated through PCR technique which gave a unique and sharp band of 919 bp in P. triticina pathotypes only. A novel gene amplification method LAMP which enables visual detection of pathogen by naked eye was developed for leaf rust pathogen. A set of six primers was designed from specific region of P. triticina and conditions were optimised to complete the observation process in 60 minutes at 65o C. The assay developed in the study could detect presence of P. triticina on wheat at 24 hpi (pre-symptomatic stage) which was much earlier than PCR without requiring thermal cycler. Sensitivity of LAMP assay developed in the study was 100 fg which was more sensitive than conventional PCR (50 pg) and equivalent to qPCR (100 fg). The protocol developed in the study was utilized for detection of leaf rust infected samples collected from different wheat fields. LAMP based colorimetric detection assay showed sky blue color in positive reaction and violet color in negative reaction after addition of 120 μM hydroxyl napthol blue (HNB) solution to reaction mixture. Similarly, 0.6 mg Ethidium bromide/ml was added to LAMP products, placed on transilluminator to witness full brightness in positive reaction and no such brightness could be seen in negative reaction mixture. Further, LAMP products spread in a ladder like banding pattern in gel electrophoresis. Our assay is significantly faster than the conventional methods used in the identification of P. triticina. The assay developed in the study shall be very much useful in the development of diagnostic kit for monitoring disease, creation of prediction model and efficient management of disease.